Infusing local culture in Singaporean animation: Developing a framework of cultural specifics from a study of contemporary cinema in Singapore. Issue 1 (1st December 2018) - Ang, Qing Sheng
Notwithstanding a materializing Singapore cinema, research attention has not been paid to how animated cultural products can make an impact on the construction of a local identity. This can be considered detrimental to the cultural promotion of a local but heterogeneous mediascape. This practice-based research attempts to outline a practical framework of cultural specifics capable of producing an animated film that is identifiably 'Singaporean' to a global audience. Resistance against the Marcusian One-Dimensional Man theory, the premise of Kenneth Paul Tan's Cinema and Television in Singapore in 2008, will be the basis of this research to understand the emergence of contemporary Singaporean films. Alfian bin Sa'at's definition of the 'heartlander', a recurring and highly relatable element in Singaporean cinema largely due to the geographical statistic of the population percentage living in Singaporean public housing (referred to as HDB), provides the social semiotics needed by the research to understand Singapore culture. Films such as Ilo Ilo by Anthony Chen and Sandcastle by Boo Junfeng will be analysed according to five indicators – setting, characters, mise en scène, language and premise – as they manifest Singaporean traits in their attempts to integrate local culture. The same indicators are used to analyse films such as 'Tatsumi' by Eric Khoo so as to locate cultural deficiency within these local animated features. 'Flats' by Ervin Han and similar animated shorts are subsequently examined as examples of attempts at infusing local culture into an animated production. The practical result of the research is presented as a production journal of an animated short explicating the socio-political aspects of local identity.